-31 DBM Sensitivity High Efficiency Rectifier For Energy Scavenging - Wong, Yan Chiew; Asli, Astrie Nurasyeila Fifie (ELSEVIER, 2018)
RF energy scavenging is capable in converting RF signals into electricity and has become a promising solution to power energy-constrained wireless networks.However,it has low power conversion efficiency especially when the harvested RF power is small.For this reason,we propose an enhanced differential-drive rectifier to improve the efficiency and the sensitivity of rectifier for energy scavenging applications.The proposed rectifier achieves dynamically controlled threshold voltage and reduces leakage current in the transistors through DTMOS transistor in differential-drive topology.The voltage boosting circuit further increases the sensitivity through step up the input signal before the signal enters the rectifier.The decoupling capacitor shunts the noise of the input signal before the signal is injected into the cross-connected gate reducing the voltage drop and maintaining the PCE of the rectifier.The rectifier is designed based on the 0.18 µm Silterra CMOS process technology.Effects of decoupling capacitors,voltage boosting circuit and output load on PCE of the rectifier have been evaluated.Technology scaling and parasitic effects to the rectifier have also been presented. Performance of N-stages proposed rectifier has been compared with the conventional BTMOS rectifier.The proposed method achieves the highest sensitivity of −31 dBm for 1, 3 and 5 stages rectifiers without the need of off-chip load capacitor.